Cancer Treatment in Islamic Traditional Medicine - Rachmat Hidayat (Arkus, 2021)
Although significant progress has been made in cancer treatment in recent decades, the effectiveness of modern therapeutic approaches is often limited by their toxic effects on other organs. In addition, many people in the world have limited or unequal access to cancer treatment services. Therefore, utilizing information from traditional medicine systems to identify alternative methods to prevent and control cancer. The use of traditional medicine can lead to the discovery of new bioactive compounds and drugs that are available, safe and affordable. In Islamic medicine, cancer is known as a disease with many treatment options. Traditional Islamic medicine suggests several strategies for cancer control and treatment. Surgical manipulation, venesection, dietary adjustment, and use of natural medicines including solid, semisolid, and liquid dosage forms by oral and external routes of administration are among these methods. This literature study will presents cancer from the perspective of traditional Islamic medicine, its aetiology and management.